Tissue‐resident MAIT cell populations in human oral mucosa exhibit an activated profile and produce IL‐17. Issue 1 (14th November 2018) - Sobkowiak, Michał J.; Davanian, Haleh; Heymann, Robert; Gibbs, Anna; Emgård, Johanna; Dias, Joana; Aleman, Soo; Krüger‐Weiner, Carina; Moll, Markus; Tjernlund, Annelie; Leeansyah, Edwin; Sällberg Chen, Margaret; et al.
Abstract: Mucosa‐associated invariant T (MAIT) cells are unconventional T lymphocytes defined by their innate‐like characteristics and broad antimicrobial responsiveness. Whether MAIT cells are part of the tissue‐resident defense in the oral mucosal barrier is unknown. Here, we found MAIT cells present in the buccal mucosa, with a tendency to cluster near the basement membrane, and located in both epithelium and the underlying connective tissue. Overall MAIT cell levels were similar in the mucosa compared to peripheral blood, in contrast to conventional T cells that showed an altered representation of CD4 + and CD8 + subsets. The major mucosal MAIT cell subset displayed a tissue‐resident and activated profile with high expression of CD69, CD103, HLA‐DR, and PD‐1, as well as a skewed subset distribution with higher representation of CD4 – /CD8 – double‐negative cells and CD8αα + cells. Interestingly, tissue‐resident MAIT cells had a specialized polyfunctional response profile with higher IL‐17 levels, as assessed by polyclonal stimulus and compared to tissue nonresident and circulating populations. Furthermore, resident buccal MAIT cells were low in perforin. Together, these data indicate that MAIT cells form a part of the oral mucosal T cell compartment, where they exhibit a tissue‐resident‐activated profile biased toward IL‐17 production. Abstract : MAIT cells are part of the human buccal mucosal immune defenses. Buccal MAIT cells are enriched in the CD4 – CD8 – phenotypic subset and can be further sub‐divided based on tissue residency markers CD103 and CD69. The buccal MAIT cells have distinct polyfunctional response profiles with high IL‐17 and low IFN‐γ production.